Fuzzy Fractional Evolution Equations and Fuzzy Solution Operators - Atimad Harir; Said Melliani; Lalla Saadia Chadli (Advances in Fuzzy Systems)
In this paper, the fuzzy fractional evolution equations of order q (FFEE) with fuzzy Caputo fractional derivative are introduced. We study the existence and uniqueness of mild solutions for FFEE under some conditions. Also, we generalize the definition of the fuzzy fractional integral and derivative order q. The fuzzy Laplace transform is presented and proved. The solvability of the problem (FFEE) and the properties of the fuzzy solution operator and its generator are investigated and developed.